Perceptions of Husband/Wife Couples about Belis (In Terms of The Subjective Well-Being) - Vera Juliana Ribka Lango; Indra Yohanes Kiling; Yeni Damayanti (Universitas Nusa Cendana, 2022)
Perception is a sensing process where the stimulus is received by the individual through the senses and then interpreted so that the individual understands the stimulus he receives. A husband/wife pair is known as a man and a woman who are united in a legal marriage to form a happy and prosperous family both physically and mentally. Marriage of husband/wife couples in NTT cannot be separated from the customs known as